Artificial Intelligence Use and Effects on Academic Task Quality and Efficiency: A Study in Higher Education - Nadia Febrian Sitanggang; Gita Magdalena Pasaribu; Grace Sihombing; Rahel Jesiska Pinem; Eka Yuli Yana; Cahaya Marsinta Sitinjak; Rini Juliana Sipahutar (PT. Global Research Collaboration, 2025)
This study explores the impact of artificial intelligence (AI) use on the quality and efficiency of academic tasks among students in higher education. The widespread integration of AI tools—such as ChatGPT, Perplexity, and other language models—has significantly influenced learning behaviors, information access, and task completion processes. The purpose of this study is to investigate how the use of AI technologies affects students’ ability to produce academic tasks with higher quality and in a more time-efficient manner, while also identifying possible drawbacks such as overreliance. A mixed-method approach was employed, combining quantitative data collected through questionnaires with qualitative insights gained from interviews. A total of 80% of the surveyed students reported frequent use of AI tools in their academic work, with ChatGPT being the most preferred platform. Results indicate that 85% of students perceived a positive impact of AI on task quality, while 75% reported improved efficiency. The qualitative data supported these findings, highlighting enhanced understanding, faster idea generation, and reduced workload. However, concerns regarding dependence and ethical use were also raised. This study concludes that AI holds substantial potential to support academic performance, but its integration must be guided by responsible usage and critical awareness in educational contexts.